Alteraciones psicológicas y psicoterapia en el contexto de la pandemia COVID-19 en niños y adolescentes - Borja Yánez, Adriana Belén (2023)
ABSTRACT: The COVID-19 pandemic had implications for human mental health, evident in the presence of psychological alterations and the use of psychotherapeutic processes to address them. This study focused on determining the psychological alterations and the psychotherapy applied during the COVID-19 pandemic context in children and adolescents. It corresponds to a bibliographic review of cross-sectional design and descriptive level. The population comprises 213 scientific articles published from 2020 to 2023 in Spanish and English. The non-probabilistic sample is composed of 77 quantitative studies. The selection criteria were applied using a bibliographic search algorithm for filtering. The sources of information were databases such as PubMed, Semantic Scholar, ScienceDirect, PubMed Central, Dialnet, Springer Link, Multidisciplinary Digital Publishing Institute, and Google Scholar, among others. The techniques used were bibliographic review and documentary quality review; in the case of instruments, the bibliographic review form and the CRF-QS matrix were employed. As for the results, several psychological alterations were found, for example, behavioral problems and hyperactivity in children, emotional regulation and stress problems in adolescents, while anxiety and depression in both age groups; psychotherapies corresponded to the cognitive-behavioral and mindfulness currents, among others; finally, some favorable aspects and difficulties in the psychotherapeutic execution were related to the use of technological tools and technical problems, respectively. In conclusion, according to the reviewed information, various psychological alterations were found, as several psychotherapeutic interventions with particularities in their application.